Paraquat-induced oxidative stress regulates N6-methyladenosine (m6A) modification of circular RNAs. (1st December 2021) - Chen, Nengzhou; Tang, Jianping; Su, Qianqian; Chou, Wei-Chun; Zheng, Fuli; Guo, Zhenkun; Yu, Guangxia; Shao, Wenya; Li, Huangyuan; Wu, Siying
Abstract: Paraquat (PQ), a widely used herbicide and well-known oxidative stress inducer, has been linked to numerous neurodegenerative diseases, but the underlying mechanism(s) remains unknown. Circular RNAs (circRNAs) have recently been reported to be associated with oxidative stress in Parkinson's disease. Herein, we performed methylated RNA immunoprecipitation and RNA sequencing assays for mouse neuroblastoma (Neuro-2a) cells and successfully established a positive link between the alteration of circRNAs driven by m 6 A modification and PQ-induced oxidative stress. We observed oxidative stress and antioxidative stress present distinct m 6 A modification pattern of circRNAs as well as biological effect. Gene ontology and pathway analysis predicted that differentially m 6 A-methylated and expressed circRNAs are highly clustered in pathways associated with function and development of nervous system, including axon cargo transport, nervous system development, long-term potentiation, and neurotrophic signaling pathways. Moreover, we demonstrated that the alteration of m 6 A-methylated circRNAs upon PQ exposure could be partially reversed by N-acetylcysteine pretreatment. The mechanistic analysis further demonstrated that N-acetylcysteine pretreatment attenuated the decreased expression of target genes (UBC and PPP2CA) induced by PQ. These findings revealed distinct patterns of differentially m 6 A-modified circRNAs, indicating that m 6 A could participate in a specific regulatory network of circRNAs to modulate the expression of downstream genes in response to PQ-induced oxidative stress. In conclusion, our work established a link between m 6 A modification of circRNAs and PQ-induced oxidative stress, and further studies are required to explore the underlying molecular mechanisms associated with PQ-induced neurotoxicity. Graphical abstract: The schematic representation of regulatory gene network of circRNAs driven by m 6 A modification in paraquat-induced oxidative stress. Image 1 Highlights: PQ exposure disrupts the N6-methyladenosine profiling of circRNA in Neuro-2a cells. CircRNA driven by m 6 A methylome is associated with PQ-induced oxidative stress response. CircRNA driven by m 6 A methylome acts as a specific regulatory gene network. Abstract : Paraquat disrupts the N6-methyladenosine profiling of circRNAs via inducing oxidative stress.